1975
DOI: 10.1017/s003329170005697x
|View full text |Cite
|
Sign up to set email alerts
|

Nostalgia: a ‘forgotten’ psychological disorder

Abstract: Nostalgia, a psychopathological condition affecting individuals who are uprooted, whose social contacts are fragmented, who are isolated and who feel totally frustrated and alienated, was first described in the 17th century and was a problem of considerable interest to physicians in the 18th and 19th centuries. by the 20th century it seemed to have disappeared, but reappeared under other labels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 7 publications
1
50
0
1
Order By: Relevance
“…78-79) In origin, then, the idea of nostalgia encapsulated a uniquely human ability to draw strength and motivation from memories of the past, especially memories relating to close others. (McCann, 1941;Rosen, 1975). Similarly, 20 th century psychodynamic theorists and clinicians regarded it as a variant of mourning, depression, or psychosis (Castelnuovo-Tedesco, 1980;Frost, 1938;Sterba, 1940).…”
Section: Historical Conceptions Of Nostalgiamentioning
confidence: 99%
See 1 more Smart Citation
“…78-79) In origin, then, the idea of nostalgia encapsulated a uniquely human ability to draw strength and motivation from memories of the past, especially memories relating to close others. (McCann, 1941;Rosen, 1975). Similarly, 20 th century psychodynamic theorists and clinicians regarded it as a variant of mourning, depression, or psychosis (Castelnuovo-Tedesco, 1980;Frost, 1938;Sterba, 1940).…”
Section: Historical Conceptions Of Nostalgiamentioning
confidence: 99%
“…The view of nostalgia as a neurological disease prevailed throughout the 17 th and 18 th centuries (Scheuchzer, 1731). In the 19 th century, people viewed nostalgia as a psychological disorder involving depression and melancholy (McCann, 1941;Rosen, 1975). Similarly, 20 th century psychodynamic theorists and clinicians regarded it as a variant of mourning, depression, or psychosis (Castelnuovo-Tedesco, 1980;Frost, 1938;Sterba, 1940).…”
Section: Historical Conceptions Of Nostalgiamentioning
confidence: 99%
“…This exposure caused "vital spirits [to] constantly surge back and forth through the nerve fibers in which the impressions of the native land are stored." 2 Today, there is a clearer sense of what causes homesickness and how it can be prevented and treated. Comprehensive historical 1,3,4 and contemporary 5,6 reviews of the literature are available.…”
Section: Introductionmentioning
confidence: 99%
“…Johannes Hofer (1994) emphasized that homesickness was an illness of younger people, who were socially lonely in unfamiliar countries, whereas Scheuchzer (1731) concluded that the cause of homesick feelings among Swiss soldiers in France was the defect of the refined Swiss air mercenaries (see Rosen, 1975). Jaspers' doctoral dissertation in 1909 named "Heimweh und Verbrechen" (Homesickness and Crime) brought up new impulses.…”
Section: Homesicknessmentioning
confidence: 99%